(3GdcJGH GdebOS hGdbQBf GdcQje hGdYde (B=s La Bible, le Coran et la science - (3HhcGj, ehQjSs 1920-1998; (3GdMGjc, efPQ,s 1944- ((3OeTb, ShQjG ;s (3OHj, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3UaMGJ ddOQGSGJ hGdfTQ hGdJhRjY,s, 2015)
(3HaVd GJSGY Cab GdOcJhQ HhcGj GdYdej hKbGaJg GdOjfjI hELGOJg GdYQHjI CZfi cJGHg GdChd, GdPj YO aGUdG aj eLGd cJH GdCOjGf GdebGQfI, hGdPj GTJgQ aj WHYJg GdYQHjI HGSe(B: "(3GdJhQGI hGdEfLjd hGdbQBf hGdYde GdMOjK,(B" (3hGdPj fTQ dChd eQI YGe (B1976. (3Ke JYOOJ WHYGJg HYO Pdc MJi dG JcGO JMUi, ceG JQLe dCcKQ ef NeSI YTQI dZI, hYO dSfhGJ cKjQI ef CcKQ GdcJH QhGLG(B. (3hfMf fbOeg Gdjhe hbO GNJQfG dg GdYfhGf GdCOb JQLeI, hgh(B: "(3GdcJGH GdebOS hGdbQBf hGdYde(B". (3HGdQZe ef GdaUhd GdeJYOOI abO QcR GdOcJhQ HhcGj aj cJGHg gPG Ydi ehVhYjf CSGSjjf, GdChd(B: (3JfGhd ajg GdQhGjGJ GdOjfjI GdcHQi eKd(B: (3Ndb GdYGde hXghQ GdEfSGf, hMGOKI GdWhaGf, hHYV GdQhGjGJ GdCNQi Mhd eXGgQ GdWHjYI hZjQgG, hbGHd cd Pdc eY eYWjGJ hMbGFb GdYde aj ReGfg GdMGVQ(B. (3CeG GdehVhY GdKGfj (B: (3agh OQGSI ebGQfI Hjf QhGjI GdbQBf hQhGjI GdJhQGI Mhd aQYhf GdNQhL, hbO MOO fbGW GdNdGa hGdGJaGb Hjf GdQhGjJjf, eQcRG Ydi QhGjI GdbQBf Mhd fLGI HOf GdaQYhf HYO ZQbg(B. (3hbO YQV BjGJ GdbQBf Ydi fJGFL GdGcJTGaGJ GdYdejI aj YUQg, Ohf RjGOI Ch fbUGf, hdPdc SjXd Yedg QGFLG, jYhO Edjg GdHGMKhf hGdbQGA djLOhG ajg HYVG ef GdYde GdPj MVfG GdESdGe GdMfja Ydi WdHg(B.s
(3GdJObjb GddZhj ESeGYjd GdcQOj ; JUeje GdZdGa e(B. (3LeGd GdCHWM(B.s
Keywords: (3GdcJH GdSeGhjIs